Benefit‐Cost Analysis of Foot and Mouth Disease Control in Large Ruminants in Cambodia. Issue 5 (10th November 2014) - Young, J. R.; Suon, S.; Rast, L.; Nampanya, S.; Windsor, P. A.; Bush, R. D.
Summary: Foot and mouth disease (FMD) is endemic in Cambodia and throughout the Greater Mekong Subregion and causes significant losses to rural smallholders owning the majority of the national large ruminant population. However, due to underreporting, paucity of knowledge of FMD impacts, limited veterinary capacity and deficits of data available for analysis, the quantifiable benefits of a national FMD control programme are unknown. To address this deficit, existing literature and research data from the 'Best practice health and husbandry of cattle, Cambodia' project conducted between 2007 and 2012, were used to develop a three‐phase analysis framework to: assess the impacts of the recent widespread FMD epizootic in Cambodia in 2010, conduct a value chain analysis of the large ruminant market and estimate the costs and benefits for a national large ruminant biannual FMD vaccination programme. A trader survey conducted in 2010–2011 provided cattle and buffalo value chain information and was matched to village herd structure data to calculate a total large ruminant farm‐gate value of USD 1.271 billion in 2010. Monte Carlo simulation modelling that implemented a 5‐year biannual vaccination programme at a cost of USD 6.3 an animal per year identified a benefit‐cost ratio of 1.40 (95% CI 0.96–2.20) when accounting for recent prices of cattle and buffalo in Cambodia and based on an expected annual incidence of 0.2 (assuming one major epizootic in the 5‐year vaccination programme). Given that the majority of the large ruminants are owned by rural smallholders, and mostly the poor are involved in agricultural employment, the successful implementation of an FMD control programme in Cambodia would be expected to avoid estimated losses of USD 135 million; equivalent to 10.6% of the 2010 farm‐gate value and contributing to important reductions in rural poverty and food insecurity.